ChemInform Abstract: Photoinduced Additive‐Free Trifluoromethylation of Aromatic Aldehydes with TMSCF3. Issue 23 (June 2015) - Sun, Jing; Peng, Xinhua; Guo, Hao
Abstract Photoirradiation not only causes the initial C—Si bond homolytic cleavage of Tms—CF3 to furnish the reactive species, but also results in the O—Si bond cleavage of the initially formed silyl ether to afford the final alcohol.